Activity of Antimycobacterial Candidate from Bacteriocins and Lactic Acid Isolated from Lactobacillus bulgaricus Against Mycobacterium tuberculosis - Prima Nanda Fauziah; Imas Latifah; Ratna Mutu Manikam; Masdianto Masdianto (Biology, Medicine, & Natural Product Chemistry, 2026)
Mycobacterium tuberculosis (Mtb) is a bacterium that causes a respiratory infectious disease known as tuberculosis. Tuberculosis (TB) is a global infectious disease that causes death. The current TB treatment method has a weakness, namely the tendency of patients to disobey the rules in taking drugs because they have to take several tablets of medicine for a long time. As a result, some strains of M.tuberculosis can strengthen themselves and become resistant to antimycobacterial drugs used during therapy. Based on these tuberculosis control problems, the WHO declared a global TB emergency. The low effectiveness of currently used antitubercular drugs encourages the development of new antimycobacterial drugs with low side effects, fast-acting, broadly targeted, and can damage the virulence properties of M.tuberculosis so that the immune system can phagocytose M.tuberculosis. A recent solution from some researchers is to induce immunomodulatory effects that help during the tuberculosis infection process, including from lactic acid bacteria (LAB). This encourages researchers to reveal the interaction of probiotic L.bulgaricus on reducing the growth of M.tuberculosis by finding the main substance with antitubercular activity to obtain optimal results. This study used sensitive M.tuberculosis strain H37Rv to get complete preliminary data. This study tested lactic acid and bacteriocin of Lactobacillus bulgaricus at concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%. M.tuberculosis bacteria were inoculated on media containing lactic acid and L. bulgaricus ATCC 11842 bacteriocin, then incubated at 37°C and observed every week from the fourth to the eighth week. Of the five concentrations of lactic acid and bacteriocin tested, only the 60-100% concentration could inhibit the growth of M.tuberculosis. In conclusion, lactic acid and bacteriocin of L. bulgaricus can hinder the growth of M.tuberculosis and can be developed into antimycobacterial drug candidates.